ANALISIS PENGELOLAAN ALOKASI DANA DESA (ADD) DAN DANA DESA (DD) TERHADAP PENGGUNAAN DANA ALOKASI DANA DESA (ADD) DAN DANA DESA (DD) DI DESA TULUNGREJO KECAMATAN DONOMULYO KABUPATEN MALANG TAHUN 2015 - Sofa, Devi Maya; Hidayat, M. Taufiq (JEA17: Jurnal Ekonomi Akuntansi, 2018)
ABSTRACTThis study aims to describe how the management of the Village Fund Allocation and the Village Fund implemented in Tulungrejo districts Donomulyo Malang district, which is in the process of planning, implementation and accountability if it is based on procedures and rules, whether the principles princip management has been able to be realized. And supporting factors and inhibitors that affect the management of the Village Fund Allocation and the village fund. In this research, the calculation to determine the amount of the management of the funds used for the fields in rural development. The results of data analysis showed that the allocation of funds and funds rural village in the village which Tulungrejo in use for four areas of rural development is the empowerment of the community amounted to 81%, the field of administration of the village of 47.16%, 41.83% field of community development and areas of development village 22.97%. In general management of the allocation of funds of the village and the village fund in Tulungrejo districts Donomulyo Malang regency less Effectively, this is proved by the persistence of the activities of management process which is still not in accordance with laws and regulations such as government regulations and rules issued by Regent Poor. Keywords: Management, Village Allocation Fund and the Village Fund